Transformation stasis phenomenon and overall transformation kinetics of low-carbon, Nb-bearing ferrous alloy - J.H Zhao; C.H Jin; Y Lai; G Yuan; X.Q Wang; K.W Zhang (Journal of Materials Research and Technology, 2020)
To illuminate the overall transformation kinetics of low-carbon, Nb-bearing ferrous Alloy (Nb ferrous alloy), a novel method was proposed to investigate the overall transformation behavior on the basis of bainitic transformation stasis theory. The stability and transformation behavior of austenite were controlled by choosing different isothermal temperatures nearby or away from the transformation start temperature (Ts), and the dilatometric variation discipline and microstructural features corresponding to different processes were investigated. Nucleation mechanisms throughout the overall transformation process were further discussed on the basis of the classical J-M-A model. Results indicate the overall transformation kinetics concerning to studied Nb ferrous alloy can be nearly separated into two stages in terms of the dilatometric variation discipline together with microstructural features, they are (a) Acicular ferrite (AF) transformation stage with relative high transformation rate at initial transformation stage, and (b) Conventional bainite (CB) transformation stage with low transformation rate in the late stage. The possible nucleation is the diffusion-controlled mechanism with regard to studied Nb ferrous alloy during isothermal temperature from 580 ℃ to 440 ℃. At the initial stage, AF nucleates on the parent austenite grain boundary or sub-grain boundary and grows in the mode of arbitrary dimensional, and the nucleation rate is decreased gradually. At the second stage, the formed AF impingements each other, and new phase nucleus attached to parent austenite grain boundary, sub-grain boundary or AF boundary begin to grow in the mode of incrassation and transform into CB, and the nucleation rate is almost zero throughout the secondary transformation stage.